Fetal fibronectin to prevent preterm birth? No way. Issue 9 (September 2016) - Lyon, Corey
Abstract : N/A: Berghella V, Saccone G. Fetal fibronectin testing for prevention of preterm birth in singleton pregnancies with threatened preterm labor: a systematic review and metaanalysis of randomized controlled trials. Am J Obstet Gynecol . 2016; pii: S0002–9378(16):30136–3.